1986
DOI: 10.1007/bf01869930
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the reconstitution of the anion transport system of the human erythrocyte membrane

Abstract: The anion transport protein of the human erythrocyte membrane, band 3, was solubilized and purified in solutions of the non-ionic detergent Triton X-100. It was incorporated into spherical lipid bilayers by the following procedure: Dry phosphatidylcholine was suspended in the protein solution. Octylglucopyranoside was added until the milky suspension became clear. The sample was dialyzed overnight against detergent-free buffer. Residual Triton X-100 was removed from the opalescent vesicle suspension by sucrose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 36 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Band 3 dimers covalently crosslinked via S-S bridges were obtained by treating the isolated protein with CuS04/ophenanthroline (13) and subsequent purification by gel filtration on a Sephacryl S-300 column (120 x 2.6 cm). Reconstitution ofthe anion-transport system in liposomes made ofegg yolk phosphatidylcholine (Lipid Products, Nutley, U.K.) was performed as described by Scheuring et al (12,14). However, Triton X-100 was substituted by nonaethylene glycol lauryl ether (15).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Band 3 dimers covalently crosslinked via S-S bridges were obtained by treating the isolated protein with CuS04/ophenanthroline (13) and subsequent purification by gel filtration on a Sephacryl S-300 column (120 x 2.6 cm). Reconstitution ofthe anion-transport system in liposomes made ofegg yolk phosphatidylcholine (Lipid Products, Nutley, U.K.) was performed as described by Scheuring et al (12,14). However, Triton X-100 was substituted by nonaethylene glycol lauryl ether (15).…”
Section: Methodsmentioning
confidence: 99%
“…Given MP = 100,000 (as in the case where there is one band 3 molecule per vesicle), vp = 0.73 ml/g, VL = 0.98 ml/g (18), and an error in density matching of 0.5 mg/ml, the Other Methods. The measurement of sulfate transport across lipid vesicle membranes, under exchange conditions, and its evaluation were performed as described earlier (12,21). In the evaluations, the anion efflux curves are fitted by the sum of a constant term (describing the contribution of protein-free vesicles) and two exponentials, representing efflux from vesicles that contain a reconstituted anion transport system [rate constant k1 (in the nomenclature of ref.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments on the reconstitution of erythrocyte band 3 protein revealed that there too, protein function and aggregation depend on the lipid-detergent composition and on the way of vesicle bilayer formation [21].…”
Section: Channel Conductivitymentioning
confidence: 99%